Hospital readmission in systemic sclerosis associated pulmonary hypertension: Results from the PHAROS registry. (17th July 2021) - Showalter, Kimberly; Pinheiro, Laura C; Jannat-Khah, Deanna; Sobol, Irina; Szymonifka, Jackie; Finik, Jackie; Steen, Virginia D; Gordon, Jessica K
Abstract: Objective: To identify individual-level factors associated with hospital readmission among individuals with SSc-associated pulmonary hypertension (SSc-PH). Methods: Individuals enrolled in the Pulmonary Hypertension Assessment and Recognition of Outcomes in Scleroderma (PHAROS) registry contributed clinical data related to SSc-PH disease severity and hospital admissions. Readmission was defined as a subsequent hospitalization within 12 months of any hospital discharge. Characteristics were compared between individuals with and without readmissions using Fisher's exact test, Wilcoxon rank-sum test, or Kruskal–Wallis test. Logistic regression was used to estimate associations between clinical predictors and likelihood of readmission. Results: Of 572 individuals with SSc-PH enrolled in PHAROS, 54% had ≥1 hospitalizations between 2005 and 2016. Among individuals ever-hospitalized, 34% had ≥1 readmission. Individuals with vs without readmissions had shorter median (IQR) time between index hospitalization date and next PHAROS visit [37 (3, 80) vs 81 (42, 136) days, P <0.001]. Index admissions related to PH or SSc ( vs non-PH/SSc related) were associated with an increased odds of 12-month readmission [aOR 6.6 (95% CI 3.2, 13.6) and aOR 2.2 (95% CI 1.1, 4.5), respectively]. Readmission was less likely among home oxygen users ( vs non-users) (aOR 0.44; 95% CI 0.22, 0.89). Race, age, sex, disease duration and disease subtype were not associated with readmission. Conclusion: The strongest predictor for 12-month readmission was an index hospitalization reason related to PH. Home oxygen use was associated with lower odds of readmission. Future studies should determine whether testing for the need for home oxygen mediates the risk of readmission in SSc-PH.